Reading for health : medical narratives and the nineteenth-century novel - Wright, Erika, 1970- (Series in Victorian Studies., 2016)
In Reading for Health: Medical Narratives and the Nineteenth-Century Novel, Erika Wright argues that the emphasis in Victorian Studies on disease as the primary source of narrative conflict that must be resolved has obscured the complex reading practices that emerge around the concept of health.